Supervisi Akademik Kepala Madrasah pada MA Cendekia Nashirul Wasathiyyah Klaten - Muhammad Sihabul Millah; Muhammad Noor Faiz (MASALIQ, 2025)
This study is motivated by the limited research on the application of humanistic-reflective academic supervision in Islamic educational institutions, despite its significant impact on enhancing teacher professionalism and improving the quality of instruction in madrasahs. The objective of this research is to analyze the practice of academic supervision at MA Cendekia Nashirul Washatiyyah Klaten, examine the implementation of humanistic and reflective approaches in the supervision process, and identify challenges in professional teacher development. A qualitative descriptive method with a case study design was employed, involving five participants—one principal and four teachers—selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation, then analyzed using the Miles and Huberman model, which includes data condensation, data display, and conclusion drawing. The findings reveal that academic supervision is conducted in a structured manner through classroom visits, review of teaching materials, and reflective discussion forums. The principal applies a humanistic-reflective approach that fosters a dialogical, supportive, and partnership-based atmosphere, where the principal acts more as a facilitator than an evaluator. This approach encourages teachers to reflect on their teaching practices and continuously develop their professional competencies. Identified challenges include limited time, administrative workload, and emotional tension experienced by teachers during supervision. The study concludes that academic supervision based on a humanistic-reflective approach positively contributes to strengthening teacher professionalism and reflects the integration of Islamic values such as ta’dib and tazkiyah in madrasah managerial practices. The implications of these findings provide a foundation for adapting holistic supervision models in other Islamic schools, especially in addressing educational challenges in the digital era.